A variable air volume control strategy for a centralized exhaust system with multiple on-off switched terminals and flow-guide devices. (June 2021) - Zeng, Lingjie; Wang, Yirui; Gao, Jun; Du, Bowen; Cao, Changsheng; Tong, Leqi; Liu, Guodong
Abstract: Exhaust system with one centralized fan and multiple terminals has been widely used for removing heat and pollutant. These systems share common problems include uneven pressure distribution within the system, insufficient exhaust at terminals, and the lack of control strategies when the condition of terminals varies. To solve those problems, an open-loop control strategy of the exhaust system with multiple on-off switched terminals and flow-guide devices is proposed. Firstly, exhaust experiments under various conditions were carried out to obtain the exhaust performance of the experimental system with/without flow-guide devices. Note that the use of flow-guide devices is a prerequisite for the realization of the simple open-loop control strategy since such devices can balance the exhaust air volume of each terminal. Secondly, CFD simulation based on experimental validation was used to expand the scope of experimental conditions and obtain the corresponding relationship between the fan frequency and the number of opening terminals, which then served as the key parameter to implement the control strategy. Note that the simulated cases could be reduced from 2 N to 2  N by grouping similar terminal working conditions, which greatly saved computing resources. Thirdly, the open-loop control strategy was established by traversing the dynamic parameters of the system under design conditions, pre-storing the data in the control system and performing data retrieval and variable frequency regulation in actual operation. Results showed that the control strategy has high stability and short response time. The exhaust air volume at each terminal can meet the exhaust demand throughout all working conditions, and the exhaust uniformity was significantly improved by combining the control scheme with the flow-guide devices. Furthermore, the system with flow-guide devices had energy-saving potential in the range of high coincidence factors. Highlights: A variable air volume control strategy is proposed. The control strategy is tested as high stability and short response time. Both the control method and flow-guide devices are important for exhaust uniformity.